Multiomic analysis of dark tea extract on glycolipid metabolic disorders in db/db mice - Wang, Caiqiong; Hu, Minghai; Yi, Yuhang; Wen, Xinnian; Lv, Chenghao; Shi, Meng; Zeng, Chaoxi (Frontiers in Nutrition, 2022)
Glycolipid metabolic disorder is a serious threat to human health. Dark tea is a kind of traditional Chinese tea, which may regulate the glycolipid metabolic disorders. Dark tea extract (DTE) is the water extraction obtained from dark tea. Compared with traditional dark tea, DTE has the benefits of convenient consumption and greater potential for promoting health. However, the regulation of DTE on glycolipid metabolism and its molecular mechanism is rarely investigated. In our study, DTE was used as raw material to study the effect and molecular mechanism of its intervention on the glycolipid metabolic in db/db diabetic mice by using multiomics analysis and modern biological techniques. (1) DTE could significantly reduce fasting glucose in diabetic db/db mice, and the higher dose group has a better effect. Histopathological examination showed that DTE slightly improve the number of islets and decrease the number of islet β cells in the pancreatic tissue in db/db mice. (2) RNA-Seq was used to analyze the gene expression in liver tissue. In terms of biological processes, DTE mainly affected the inflammation and fatty acid metabolism. In terms of cell components, the lipoprotein and respiratory chain are mainly affected. In the aspect of molecular function, DTE mainly affected the redox related enzyme activity, iron ion binding and glutathione transferase. Arachidonic acid metabolism pathway, glutathione metabolism and PPAR signaling pathway were enriched by DTE with the results of KEGG pathway enrichment. In addition, real-time PCR results confirmed that DTE could significantly activate key genes of PPAR signaling pathway like Fabp1, Cyp4a1, Ehhadh, Cyp4a32, Aqp7 and Me1. (3) 16s rDNA showed that DTE could significantly decrease the ratio of Firmicutes/ Bacteroidetes and the abundance of Proteobacteria, and increased the relative abundance of Verrucomicrobia at the phylum level. At the genus level, the relative abundance of Akkermansia, Prevotellaceae, Bacteroides and Alloprevotella was significantly increased after DTE treatment. This study provides multiomics molecular evidence for the intervention effect of DTE on abnormal glucose and lipid metabolism and the application of precise nutritional diet intervention of dark tea extract.